Development of Digital Assessment of Science Literacy Based on Socioscientific Issues (ALIS SSI) for Elementary School Students - Mahya, Yogi Muthohir Zuhad; Desstya, Anatri (Universitas Muhammadiyah Surakarta, 2024)
Purpose: 1) To describe the assessment that has been applied in IPAS learning in ele-mentary schools, 2) Describe the specifications of the Digital Assessment of Science Literacy Based on Socioscientific Issues (ALIS SSI), and 3) Analyze the validity and reliability of the Digital Assessment of Science Literacy Based on Socioscientific Issues (ALIS SSI). Methodology: This type of re-search is Research and Development with the ADDIE model (analysis, de-sign, development, implementation, evaluation) which is only limited to the development stage. The subjects of this research were teachers and grade IV students at SD IT Muhammadiyah Al-Kautsar Kartasura, MI Muhammadiyah PK Kartasura, SDN Bratan 3, and validators. Methodology: Data collection techniques were carried out by observation, interviews, documentation, product validation sheets, and try out. Data analysis tech-niques used data reduction, data presentation, conclusion drawing, descrip-tive quantitative, and Pearson Correlation validity test and Cronbach's Alpha reliability. The data validity test used triangulation of sources and techniques. Results: 1) Learning assessments applied by teachers are still conventional (paper and pencil), not yet digital-based and there are no assessments made specifically to measure students' science literacy. 2) Digital Assessment of Science Liter-acy Based on Socioscientific Issues (ALIS SSI) can be applied with android type smartphones and consists of 4 menus. This assessment aims to measure science literacy. 3) The development results obtained 14 valid and reliable items with a Pearson Correlation validity score of 0.609-0.896 and Cronbach's Alpha reliability between 0.725-0.829. The product validity test obtained a value of 87.5% including very feasible criteria. Thus the Digital Assessment of Science Literacy Based on Socioscientific Issues (ALIS SSI) can be used to measure the science literacy of grade IV elementary school students on the material Love Nature and the Environment. Applications/Originality/Value: In using this assessment, it is necessary to prepare the learning process that must integrate socioscientific issues, with the hope that not only science liter-acy can be measured but also morals and ethics towards the environment.